2013
DOI: 10.1016/j.asoc.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Granular computing neural-fuzzy modelling: A neutrosophic approach

Abstract: Granular computing is a computational paradigm that mimics human cognition in terms of grouping similar information together. Compatibility operators such as cardinality, orientation, density, and multidimensional length act on both in raw data and information granules which are formed from raw data providing a framework for human-like information processing where information granulation is intrinsic. Granular computing, as a computational concept, is not new, however it is only relatively recent when this con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 26 publications
1
34
0
Order By: Relevance
“…A type2-fuzzy logic system (T2-FLS) is the same as a type1-fuzzy logic system (T1-FLS) [33][34][35], which is characterised by linguistic IF. .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A type2-fuzzy logic system (T2-FLS) is the same as a type1-fuzzy logic system (T1-FLS) [33][34][35], which is characterised by linguistic IF. .…”
Section: Methodsmentioning
confidence: 99%
“…This is the same MLP-NN modelling approach that was used in the study reported in [24]. The type-1 radial basis function neural network (T1-RBF-NN) has also five rules (for fair comparison purposes) and is trained via an adaptive error back propagation (BP) learning algorithm [33,34,48].…”
Section: Comparative Studymentioning
confidence: 99%
“…For example, ECSFS [11] and SSEM [10] models are error-reducing evolving methods, and boundary constraints are used in the evolving method. Consequently, many studies on fuzzy granular approach focus on the improvement of interpretability constraints (or decision boarders) to achieve a low model error [16,17,20,21,25]; this is a second significant consideration for granular computing. Therefore, evolving granule approach and interpretability constraint are important to coexist concurrently.…”
Section: Authorsmentioning
confidence: 99%
“…Furthermore, the concept of justifiable granularity and allocation of information granularity [16,17,20,21,25] consist of the fundamental blocks of granular computing. The optimal allocation of information granularity [21,48] can be employed to group decision making problems [22][23][24] in which the initial preferences from the decision maker can be adapted to reach higher agreement [48].…”
Section: Authorsmentioning
confidence: 99%
“…This work is shown to improve the classification performance and to control the linguistic uncertainty produced throughout the construction of the inference mechanism. In [12], Solis and Panoutsos proposed an RBF-NN-based neutrosophic framework for the prediction of heat treated steel properties where a neutrosophic index was designed in order to measure the inclusion uncertainty throughout the granulation process used for estimating the parameters of the RBF-NN. Nevertheless, the design of logic-driven systems and interpretable models based on RUs has been an ongoing challenge in the area of modelling.…”
Section: Introductionmentioning
confidence: 99%